2005
DOI: 10.2174/1566524054022585
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Responses Induced by the Capsular Polysaccharide of Cryptococcus neoformans Differ Depending on the Presence or Absence of Specific Protective Antibodies

Abstract: The capsule of Cryptococcus neoformans, the principal virulence factor of this fungus, is composed primarily of polysaccharide. The predominant component of the polysaccharide capsule is glucuronoxylomannan (GXM), a compound with potent immunoregulatory properties. GXM is bound and internalized by natural immune cells affecting innate and subsequent adaptive immune response. The cellular pattern recognition receptors involved in GXM binding include toll-like receptor (TLR)4, CD14, TLR2, CD18, Fc gamma receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…Our studies, as well as others, demonstrated that the GXM-mAb complex counteracts the suppression exerted by GXM (20,37,42). This suggests an essential role for macrophages in acquiring and storing GXM in various organs and is consistent with previous observations of GXM accumulation inside tissue macrophages in vivo (43,44).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our studies, as well as others, demonstrated that the GXM-mAb complex counteracts the suppression exerted by GXM (20,37,42). This suggests an essential role for macrophages in acquiring and storing GXM in various organs and is consistent with previous observations of GXM accumulation inside tissue macrophages in vivo (43,44).…”
Section: Discussionsupporting
confidence: 92%
“…7). It is noteworthy that Fc␥RIIA senses the GXM-mAb complex, providing an explanation for the previously reported extraordinary activation of innate and adaptive immune response documented for this Ab (37). This is consistent with phosphorylation of IB␣; however, it is plausible that other receptors such as Fc␥RIII and Fc␥RI are engaged by the GXM-mAb complex and cooperate to trigger activation signals.…”
Section: Discussionsupporting
confidence: 84%
“…GXM exerts a variety of deleterious effects on host immunity, including inhibition of leukocyte migration, reduced costimulatory molecule expression, altered cytokine expression, and reduced antibody responsiveness (17,46,66). Perhaps of the greatest relevance to virulence, the cryptococcal capsule inhibits phagocytosis (32,72).…”
Section: The Landscape: the Cryptococcal Capsulementioning
confidence: 99%
“…These acapsular strains were avirulent in mice, and they were readily ingested by phagocytes, but their ingestion could be inhibited by the addition of purified polysaccharide (3). The effect of the C. neoformans polysaccharide capsule on the host cells can be summarized as follows: it interferes with phagocytosis, blocks the recruitment of inflammatory cells, increases costimulatory molecules, suppresses the delayed-type-hypersensitivity response, and reduces the antibody production in response to fungal infection (11,43).Dendritic cells (DC) are professional antigen-presenting cells that can initiate the innate and adaptive immune response against invading pathogens, thus enabling the decoding of microbe-associated information which then results in qualitatively different adaptive T-helper responses in vitro and in vivo (2, 8).Mouse DC internalize C. neoformans cells via the mannose receptor and the Fc receptor for immunoglobulin G (Fc␥R). The cryptococcal antigens are then presented to T cells, which undergo proliferation and activation (40).…”
mentioning
confidence: 99%
“…These acapsular strains were avirulent in mice, and they were readily ingested by phagocytes, but their ingestion could be inhibited by the addition of purified polysaccharide (3). The effect of the C. neoformans polysaccharide capsule on the host cells can be summarized as follows: it interferes with phagocytosis, blocks the recruitment of inflammatory cells, increases costimulatory molecules, suppresses the delayed-type-hypersensitivity response, and reduces the antibody production in response to fungal infection (11,43).…”
mentioning
confidence: 99%